Séries de potência e sua aplicação na resolução de Edo’s - Barbosa, Mayke Sombra (Universidade Federal Rural do Semi-Árido, 2019)
The work referent presents as main goal an alternative means for resolution and Differential Equations through the Potency Séries. The research is based on a bibliographic sequence. We used as source of books research and Work of Conclusion of Course of other authors for the bibliographical complementation. In advance of the main goal of the same was portrayed a little of the history of the Sequences and Series of Differential Equations. We recall some concepts considered as prerequisite to our study topic, all the theorems on Sequences and Séries, Potency Séries and some of the most important on Equations were defined and demonstrated. Differences intended to understand these to better understand the work. The goal of this is not only to obtain a diploma, but also to serve as study material for future readers of the area. It is concluded that the presented method is effective because it is an alternative way to solve conventional equations and others it can not be solved by the common methods of Differential Calculus and Integral.
Monografia
Keywords: Equações diferenciais; Sequências e séries; Séries de potência; Differential equations; Potency séries; Sequences and séries; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA